HOME-BASED EXPERIMENT: STUDENTS’ RESPONSES ABOUT INDEPENDENT PRACTICUM AT HOME DURING ONLINE LEARNING - Putra, Nanda Syah; Desmiawati, Desi (Didaktika Biologi: Jurnal Penelitian Pendidikan Biologi, 2023)
This study aimed to reveal students’ responses to the implementation of home-based experiments on photosynthesis materials. The research sample consisted of 1 class that implemented home-based experiment learning, with the number of students involved being 26 students, which was determined using convenience sampling technique.The student response measurement scale used the Guttman scale, which demanded an unequivocal answer from the student to the given question. Students were given a choice of "yes" or "no" answers. Student response questionnaires consisted of 3 aspects, namely students' attitudes toward home-based experiment learning, students' interest in home-based experiment learning, and student's understanding of learning materials after home-based experiment learning. Based on the student practicum report related to the success of carrying out the practicum as evidenced by the drawings of the observation results, the application of home-based experiments by carrying out the Sach experiment practicum showed satisfactory results where in general students completed experimental activities well. Then, the application of home-based experiments received a positive response from students which could encourage the improvement of student cooperation ability, student independent ability, and student enthusiasm as confirmed in the questionnaire items. This study can be a reference and encouragement for science teachers to be able to apply home-based experiments in the learning process as a variety of learning methods, especially during the Covid-19 pandemic. Penelitian ini bertujuan mengungkapkan pandangan dan pendapat siswa terhadap penerapan praktikum dengan home-based experiment pada materi fotosintesis. Sampel penelitian terdiri dari 1 kelas yang mengimplementasikan pembelajaran dengan home-based experiment, dengan jumlah siswa yang terlibat adalah 26 siswa, yang ditentukan secara convenience sampling technique. Pengukuran respon siswa menggunakan skala Guttman dimana menuntut jawaban pasti dari siswa pada pernyataan yang diberikan. Siswa diberikan pilihan jawaban “ya” atau “tidak”. Kuesioner respon siswa terdiri dari 3 aspek, yaitu sikap siswa terhadap pembelajaran dengan home-based experiment, minat siswa terhadap pembelajaran dengan home-based experiment, dan pemahaman siswa terhadap materi pembelajaran setelah penerapan home-based experiment. Berdasarkan pada laporan praktikum siswa terkait dengan keberhasilan melaksanakan praktikum yang dibuktikan dengan gambar hasil pengamatan, maka penerapan home-based experiment dengan melaksanakan praktikum percobaan Sach menunjukkan hasil yang memuaskan dimana pada umumnya siswa menyelesaikan kegiatan eksperimen dengan baik. Kemudian, penerapan home-based experiment mendapatkan respon positif dari siswa dimana dapat mendorong peningkatan kemampuan kerjasama siswa, kemampuan mandiri siswa, dan antusiasme siswa sebagaimana telah dikonfirmasi pada item kuesioner. Penelitian ini dapat menjadi acuan dan dorongan bagi guru IPA untuk bisa menerapkan home-based experiment dalam proses pembelajaran sebagai salah satu variasi metode belajar terutama di masa pandemi Covid-19.